2018
DOI: 10.1007/s12665-018-7704-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture remote-sensing applications for identification of flood-prone areas along transport infrastructure

Abstract: The expected increase in precipitation and temperature in Scandinavia, and especially short-time heavy precipitation, will increase the frequency of flooding. Urban areas are the most vulnerable, and specifically, the road infrastructure. The accumulation of large volumes of water and sediments on road-stream intersections gets severe consequences for the road drainage structures. This study integrates the spatial and temporal soil moisture properties into the research about flood prediction methods by a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The TPR shows the percentage of landslide pixels accurately categorized as landslide occurrences, and the FPR indicates the percentage of non-landslide pixels wrongly identified as landslides [111]. The Formulas (12) and (13) were used to calculate the TPR and FPR:…”
Section: Methods For Validating the Modelsmentioning
confidence: 99%
“…The TPR shows the percentage of landslide pixels accurately categorized as landslide occurrences, and the FPR indicates the percentage of non-landslide pixels wrongly identified as landslides [111]. The Formulas (12) and (13) were used to calculate the TPR and FPR:…”
Section: Methods For Validating the Modelsmentioning
confidence: 99%
“…The use and processing of numerous spatial data, satellite images, and aerial photographs in geographic information systems (GIS) for the selection of appropriate check dam sites over large watershed scales are computationally costly [25,26]. Straightforward site identification for a more efficient management support may be facilitated by an analytic hierarchy process (AHP) in GIS [27,28] based on some geomorphometric and topo-hydrological watershed factors [29,30] that, to our best knowledge, yet remain to be considered for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Because of lack of reasonable and trustworthy techniques, most spatial modeling studies reported in the literature use a simple random method to select absence samples in different fields, for example, groundwater potential [3,5,10,[13][14][15][16], landslide susceptibility [1,[17][18][19][20][21], gully erosion susceptibility [22][23][24][25], land subsidence susceptibility [26][27][28][29][30][31], and flood susceptibility [18,[32][33][34][35][36][37]. However, the random sampling method has some drawbacks.…”
Section: Introductionmentioning
confidence: 99%